Rapid cooling and exhumation in the western part of the Mesoproterozoic Albany-Fraser Orogen, Western Australia - Scibiorski, E.; Tohver, E.; Jourdan, Fred (Elsevier, 2014)
The Albany-Fraser Orogen of southwestern Australia is an understudied orogenic belt, which is interpreted to record the Mesoproterozoic suturing of the Yilgarn Craton of Western Australia to the Mawson Craton of East Antarctica during Rodinia assembly. Previous U-Pb geochronology has dated peak amphibolite to granulite-facies metamorphism in the orogen at ca 1180Ma. Here, we report the first 40Ar/39Ar thermochronology of hornblende, biotite and muscovite grains from a 360km transect across the western Albany-Fraser Orogen, and uncover a record of strikingly fast syn-orogenic cooling and exhumation.To the north, muscovites from the Northern Foreland record cooling at ca 1159. Ma. In the central and southern domains of the orogen, the Biranup and Nornalup Zones, hornblende yields ca 1169. Ma cooling ages, and biotite yields ca 1172-1144. Ma cooling ages. The new cooling ages imply that the three domains were exhumed rapidly following peak metamorphism at ca 1180. Ma, attained a similar structural level by ca 1159. Ma, and have experienced a uniform exhumation history since that time. To constrain mineral closure temperatures and post-peak metamorphic cooling rates, we conducted a Monte Carlo simulation, which fully propagates uncertainty and minimises error correlations. Modelling of cooling from hornblende to biotite closure temperatures (ca 585. °C and 365. °C respectively) in the Nornalup and Biranup Zones yields fast cooling rates of 33-9+17°C/Ma and 22-5+7°C/Ma respectively. These fast cooling rates imply rapid exhumation in an active tectonic setting undergoing peak metamorphism.Although the structural evolution of the Albany-Fraser Orogen remains poorly constrained, the transpressional tectonic activity associated with deformation in the western part of the Albany-Fraser Orogen may have been an active driver of this fast exhumation. This is distinctly different from exhumation models for granulite-facies domains in other Mesoproterozoic orogens, which typically experience post-orogenic, slow 1-5. °C/Ma cooling, driven by mechanisms such as orogenic collapse and erosion. We consider that the observed differences reflect the interpreted syn-tectonic transpressional exhumation history of the Albany-Fraser Orogen, which is an underrepresented tectonic regime in the Mesoproterozoic cooling record.